3-Dimensional cuboid structured ZnFe2O4@C nano-whiskers as anode materials for lithium-ion batteries based on the in situ graft polymerization method. Issue 99 (11th October 2016) - Qu, Lina; Hou, Xianhua; Mao, Junwei; Ru, Qiang; Hu, Shejun; Liu, Xiang; Lam, Kwok-ho
Abstract : 3-Dimensional cuboid structured ZnFe2 O4 @C nano-whiskers anode materials have been successfully synthesized via an in situ graft copolymerization method and the subsequent calcination process. Abstract : 3-Dimensional cuboid structured ZnFe2 O4 @C nano-whiskers anode materials have been successfully synthesized via an in situ graft copolymerization method and the subsequent calcination process. Polystyrene-acrylonitrile (PSA) serves as the coating layer, which plays an important role in the calcination process. The final electrode materials were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The results of electrochemical tests demonstrate an excellent electrochemical performance, including good rate capability (over 700 mA h g −1 at the current density of 3.2 A g −1 ) and good cycling performance (a reversible capacity of 1722 mA h g −1 after 120 cycles with coulombic efficiency of 98.4%). Therefore, we believe that the proposed work may be a potential method to assist ZnFe2 O4 to be a quite promising alternative anode material for lithium-ion batteries (LIBs).